Derivation of Load Peak Voltage, Power Consumption and Potential Energy Management in a Thyristor Controlled Marx Impulse Generator for Capacitor Discharge Application - Toudeshki, Arash; Mariun, Norman; Hashim, Nizam; Noor Izzri, Abdul Wahab; Hojabri, Mojgan; Ali Sai’d, Yunusa; Saadatian, Omidreza; Muhammad, Mansoor; Saadatian, Elham (2013)
Calculation of the load peak voltage, potential energy and power consumption of a Marx impulse generator, as a function of time, are presented. The equations are generalized and can be used to the design of any type of n-stage Marx impulse generator. The results were validated for a thyristor controlled Marx impulse generator with a maximum number of stages of 10 and 3 kV input DC voltage, which used 1 MΩ resistors and 33 nF capacitors in its topology.